Carbon fiber structure battery negative electrode material, preparation method, negative electrode plate and lithium ion battery

By covering carbon nanotubes and polydopamine on the surface of the carbon fiber and forming a porous structure through heat treatment, the problem of insufficient mechanical strength and electrochemical performance of the negative electrode material of the existing carbon fiber structure battery is solved, and the high mechanical strength and electrochemical performance is achieved, and the battery performance is significantly improved.

CN119560535AActive Publication Date: 2025-03-04SUZHOU INST OF NANO TECH & NANO BIONICS CHINESE ACEDEMY OF SCI
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411742713.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-04
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The negative electrode materials of existing carbon fiber structure batteries cannot have high mechanical strength and high electrochemical properties, and the cladding layer is prone to fall off, affecting the mechanical and interface performance of the battery.

Method used

Carbon nanotubes and polydopamine are coated on the surface of the carbon fiber. Through the strong interaction between polydopamine and carbon nanotubes and carbon fibers, the mechanical and electrochemical properties of the material are improved, and porous structures are formed through heat treatment to enhance the interface performance.

Benefits of technology

The mechanical strength and electrochemical properties of carbon fiber negative electrode materials are significantly improved, the interface bonding strength between the negative electrode materials and resin/electrolyte materials is improved, and the mechanical properties, rate performance and specific capacity of lithium-ion batteries are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560535A_ABST
    Figure CN119560535A_ABST
Patent Text Reader

Abstract

The invention relates to a carbon fiber structure battery negative electrode material, a preparation method, a negative electrode plate and a lithium ion battery. The carbon fiber structure battery negative electrode material comprises carbon fibers, carbon nanotubes and polydopamine. The carbon nanotube and the polydopamine are coated on the surface of the carbon fiber; the polydopamine is used for connecting the carbon fibers and the carbon nanotubes in a strong interaction manner between the carbon fibers and the carbon nanotubes. The carbon nanotubes are selected to modify the carbon fibers, and the carbon nanotubes and the polydopamine are coated on the surfaces of the carbon fibers, so that the specific capacity of the structural battery negative electrode is improved while the mechanical performance and the interface performance are improved. Wherein the polydopamine is used for connecting the carbon fibers and the carbon nanotubes in a strong interaction manner between the carbon fibers and the carbon nanotubes, so that the binding power between the carbon nanotubes and the carbon fibers is further improved, and the carbon fibers have good mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of structural battery negative electrode materials, and in particular to a carbon fiber structural battery negative electrode material, a preparation method, a negative electrode sheet and a lithium ion battery. Background Art

[0002] Carbon fiber has good electrical conductivity (1000S·cm -1 ), excellent mechanical properties (high specific strength, high modulus, high compressive strength, high shear modulus) and low density (1.7-2.0g / cm 3 ) Advantages of lightweight As a necessary component of structural battery electrodes, it can store energy and withstand mechanical loads. However, the surface of carbon fiber is inert and the interface performance with resin is poor; in addition, as the negative electrode of structural batteries, the specific capacity of carbon fiber is low, making it difficult to give full play to the advantages of carbon fiber in structural batteries.

[0003] Currently, structured lithium-ion batteries (LIBs) generally use carbon fibers (CFs) as multifunctional anode materials to provide Li + However, the development of structured LIBs is hampered by the defects of CF, such as low specific capacity, chemically inert surface, and significant volume expansion during lithiation.

[0004] It has been reported that iron oxide (Fe3O4) crystals are synthesized on acidified carbon fibers by in-situ growth, and then a layer of PDA molecules is coated on the surface to adapt to the deformation of Fe3O4 due to volume expansion. At the same time, Fe3O4 also brings a large specific capacity to the structural battery. However, under this method of preparation, the carbon fiber is damaged due to acidification, and the bonding force between Fe3O4 and carbon fiber, and between PDA and iron oxide is very weak, which is not conducive to the mechanical properties and interface properties of the structural battery. Moreover, the ability of Fe3O4 particles to conduct electrons is weak, which is not conducive to the rate performance of the structural battery.

[0005] There are also reports that graphite powder, conductive carbon black and binder PVDF are mixed in a certain proportion to make a slurry, which is then coated on the surface of carbon fiber cloth to prepare the negative electrode. However, the battery capacity brought by this method has an upper limit, and a thick layer of active material is not conducive to the mechanical properties and interface properties of the battery. At the same time, the gaps between carbon fiber cloths are not conducive to the electron transmission between fibers.

[0006] Since the carbon fiber negative electrode materials in the prior art cannot have both excellent mechanical strength and good electrical conductivity, how to develop a carbon fiber structure battery negative electrode material with both high mechanical strength and high electrochemical performance has become a problem that needs to be solved urgently. Summary of the invention

[0007] In order to solve the above technical problems, the purpose of the present invention is to provide a carbon fiber structure battery negative electrode material, a preparation method, a negative electrode plate and a lithium ion battery. The carbon fiber structure battery negative electrode material of the present invention has high mechanical strength and excellent electrochemical properties, and solves the problem of easy shedding of the coating layer. The negative electrode plate of the present invention has excellent mechanical and electrical properties, and can significantly improve the problem of poor interface bonding strength between the carbon fiber negative electrode material and the resin / electrolyte material. Its excellent mechanical strength can also be used as a positive and negative electrode current collector. The provided lithium ion battery not only has excellent mechanical properties, but also has excellent rate performance and high specific capacity.

[0008] To achieve this object, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a carbon fiber structure battery negative electrode material, which comprises carbon fiber, carbon nanotubes and polydopamine; the carbon nanotubes and polydopamine are coated on the surface of the carbon fiber to form a carbon nanotube and polydopamine coating layer; the polydopamine connects the carbon fiber and the carbon nanotube in the form of a strong interaction between the carbon fiber and the carbon nanotube.

[0010] The present invention selects carbon nanotubes to modify carbon fibers, and carbon nanotubes and polydopamine are coated on the surface of carbon fibers, thereby improving mechanical properties and interface properties while increasing the specific capacity of the negative electrode of the structural battery. In addition, this design can also be used for the current collector of the positive electrode of the structural battery, because compared with aluminum foil, carbon nanotube-modified carbon fibers have not only good electrical conductivity, but also excellent mechanical properties and deformation resistance of positive electrode active materials, wherein polydopamine connects carbon fibers and carbon nanotubes in the form of strong interaction between carbon fibers and carbon nanotubes, further improving the bonding force between carbon nanotubes and carbon fibers, so that it has good mechanical properties.

[0011] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0012] Preferably, the carbon fiber structure battery negative electrode material has a porous structure.

[0013] The porous structure contained in the carbon fiber structure battery negative electrode material of the present invention can increase the specific surface area of ​​the material, improve the interface contact between the battery negative electrode and the resin material, and at the same time improve the wetting effect of the electrolyte, increase the contact between the electrolyte and the electrode material, and improve the electrochemical stability of the battery.

[0014] Preferably, the thickness of the carbon nanotube and polydopamine coating layer is 20-250nm, for example, it can be 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm, 200nm, 210nm, 220nm, 230nm, 240nm or 250nm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0015] Preferably, the carbon nanotubes include single-walled carbon nanotubes or multi-walled carbon nanotubes.

[0016] In a second aspect, the present invention provides a method for preparing the carbon fiber structure battery negative electrode material as described in the first aspect, the preparation method comprising the following steps:

[0017] (1) uniformly mixing carbon nanotubes, polyvinyl pyrrolidone and water to obtain a CNT / PVP solution;

[0018] (2) mixing a pH buffer with a CNT / PVP solution, adjusting the pH of the solution, and then adding dopamine hydrochloride to obtain a CNT / PVP / DA solution; impregnating the CNT / PVP / DA solution into the pretreated carbon fiber, and obtaining a CF@PDA@CNT material through reaction, washing, and drying;

[0019] (3) The obtained CF@PDA@CNT material is subjected to heat treatment to obtain the carbon fiber structure battery negative electrode material.

[0020] The present invention utilizes the synergistic effect of polydopamine (PDA) and polyvinyl pyrrolidone (PVP) to comprehensively improve the mechanical properties and electrical properties of carbon fiber materials. Among them, the addition of carbon nanotubes improves the conductivity of a single carbon fiber and enhances the electronic conduction between carbon fibers in the resin electrolyte; the present invention uses polyvinyl pyrrolidone as a dispersant to promote the dispersion of carbon nanotubes. Compared with other dispersants, on the one hand, PVP can form a stronger interaction with dopamine in a dopamine solution, attracting dopamine to adhere and polymerize along CNT with PVP as the center, and on the other hand, PVP can be removed in the subsequent heat treatment stage, thereby leaving pores in the negative electrode material. The formation of pores increases the specific surface area of ​​the carbon fiber negative electrode material, improves the wettability of the interface, and thus improves the contact between the electrolyte and the carbon fiber negative electrode material.

[0021] In addition, the addition of PDA can achieve modification on a single carbon fiber without damage, thereby enhancing the interface performance between the carbon fiber negative electrode material and the resin electrolyte; after the CNT / PVP / DA solution is impregnated onto the carbon fiber, dopamine hydrochloride undergoes a polymerization reaction, during which polydopamine can connect the carbon nanotubes and the carbon fiber, so that the carbon nanotubes can be tightly connected to the surface of the carbon fiber and form a strong and stable coating together with the polydopamine, so that the carbon nanotubes will not fall off during the battery cycle; on this basis, impurities are removed by heat treatment, and at the same time, part of the polydopamine undergoes a crystal transformation, thereby obtaining a carbon fiber negative electrode material with higher specific capacity and better rate performance.

[0022] Preferably, the mass ratio of the carbon nanotubes, polyvinyl pyrrolidone and water is (1-2):(0.5-5):(1-10), for example, it can be 1:1:1, 1:1:2, 1:2:1, 2:1:1, 2:2:1, 1:1:2, 1:2:3, 2:1:4, 2:2:6, 1:3:10, 1:3:2, 1:3:3, 1:3:10, 1:4:10 or 2:1:2, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0023] The present invention further controls the mass ratio of carbon nanotubes, polyvinyl pyrrolidone and water to (1-2):(0.5-5):(1-10) to obtain a uniformly dispersed carbon nanotube dispersion. By adjusting the mass ratio of carbon nanotubes and polyvinyl pyrrolidone, the dispersion state of the carbon nanotubes in the dispersion and the distribution state on the carbon fibers in the later stage can be controlled.

[0024] Preferably, the diameter of the carbon nanotubes is 7nm-20nm, for example, it can be 7.1nm, 7.2nm, 7.3nm, 7.4nm, 7.5nm, 7.6nm, 7.7nm, 7.8nm, 7.9nm, 8.0nm, 8.1nm, 8.2nm, 8.3nm, 8.4nm, 8.5nm, 8.6nm, 8.7nm, 8.8nm, 8.9nm, 9.0nm, 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, 16nm, 17nm, 18nm, 19nm or 20nm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0025] Preferably, the length of the carbon nanotubes is 10μm-200μm, for example, it can be 10μm, 20μm, 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 110μm, 120μm, 130μm, 140μm, 150μm, 160μm, 170μm, 180μm, 190μm or 200μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0026] Preferably, the mixing method includes ultrasound and high-pressure homogenization dispersion.

[0027] Preferably, the mixing is firstly carried out by ultrasonic dispersion and then by high-pressure homogenization dispersion.

[0028] In order to improve the dispersion uniformity of carbon nanotubes, the present invention uses ultrasonic dispersion plus a high-pressure homogenizer to disperse the carbon nanotubes, thereby improving the dispersion effect and efficiency.

[0029] Preferably, the ultrasonic time is 10 min-20 min, for example, 10 min, 12 min, 14 min, 16 min, 18 min or 20 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0030] Preferably, the dispersion pressure of the high-pressure homogenizer is 300 bar-500 bar, for example, 300 bar, 350 bar, 400 bar, 450 bar or 500 bar, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0031] Preferably, the dispersion time of the high-pressure homogenizer is 20 min-30 min, for example, it can be 20 min, 22 min, 24 min, 26 min, 28 min or 30 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0032] Preferably, the carbon fiber pretreatment method comprises the following steps:

[0033] The carbon fiber is heated to 400-500°C at a heating rate of 5-10°C / min, and calcined for 20-60 minutes to remove the glue, thereby obtaining the pretreated carbon fiber.

[0034] The heating rate may be, for example, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0035] The calcination temperature may be, for example, 400° C., 420° C., 440° C., 460° C., 480° C. or 500° C., but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0036] The calcination time can be, for example, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min or 60 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0037] The carbon fiber of the present invention is pretreated to remove the sizing agent on the surface of the carbon fiber, so that the PDA can directly connect the carbon fiber and the carbon nanotube, which helps to improve the interface bonding strength and electrical conductivity between the carbon fiber and the carbon nanotube.

[0038] Preferably, the pH buffer in step (2) comprises tris(hydroxymethyl)aminomethane.

[0039] Preferably, the pH of the solution is adjusted to 8.0-9.0, for example, 8.1, 8.2, 8.3, 8.4, 8.5, 8.6, 8.7, 8.8, 8.9 or 9.0, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0040] Preferably, the mass ratio of CNT to dopamine hydrochloride in the CNT / PVP / DA solution is (1-2):(1-2), for example, it can be 1:1, 1:1.5, 1:2, 1.5:1, 1.5:2 or 2:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0041] The present invention further controls the mass ratio of CNT to dopamine hydrochloride in the CNT / PVP solution to be (1-2):(1-2) to regulate the progress of the subsequent reaction and the thickness of the coating layer. At the same time, since the polydopamine generated by the reaction acts as a bridge between the carbon nanotubes and the carbon fibers to connect them, the addition amount of dopamine hydrochloride will affect the stability of the coating layer. When the addition amount of dopamine hydrochloride is too much, the thickness of the coating layer will be too thick, and the excess polydopamine will form a coating layer on the outer layer of the carbon nanotubes, which will hinder the transmission of electrons and is not conducive to the improvement of the conductivity of the negative electrode material.

[0042] Preferably, the impregnation step comprises: pouring the solution into a rectangular tank, fixing the pretreated carbon fiber in the rectangular tank, the reaction temperature is 25° C.-40° C., and the reaction time is 5 h-8 h.

[0043] The temperature of the impregnation reaction can be, for example, 25°C, 26°C, 27°C, 28°C, 29°C, 30°C, 31°C, 32°C, 33°C, 34°C, 35°C, 36°C, 37°C, 38°C, 39°C or 40°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0044] The present invention immediately contacts the mixed CNT / PVP / DA solution with carbon fiber. During the process, a polymerization reaction of dopamine hydrochloride occurs. After the reaction, polydopamine is connected with carbon nanotubes and carbon fiber through adhesion, so that the carbon nanotubes can be firmly fixed on the carbon fiber. During the reaction, the temperature and time of the reaction are controlled, and the polymerization degree of dopamine hydrochloride is controlled, so as to form a structure in which polydopamine and carbon nanotubes jointly cover the carbon fiber.

[0045] The reaction time of the impregnation may be, for example, 5 h, 6 h, 7 h or 8 h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0046] Preferably, the cleaning solvent in step (2) comprises water.

[0047] Preferably, the drying temperature in step (2) is 60°C-80°C, for example, 60°C, 65°C, 70°C, 75°C or 80°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0048] Preferably, the drying time in step (2) is 12 h-24 h, for example, 12 h, 14 h, 16 h, 18 h, 20 h, 22 h or 24 h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0049] Preferably, the temperature of the heat treatment in step (3) is 400°C-2000°C, for example, it can be 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C, 1600°C, 1700°C, 1800°C, 1900°C or 2000°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable, preferably 400°C-750°C.

[0050] The purpose of the heat treatment step of the present invention is to remove unreacted impurities and completely remove PVP to form a porous structure on the surface of the carbon fiber. In addition, within this temperature range, part of the polydopamine can undergo partial graphitization, which can further improve the conductivity of the carbon fiber negative electrode material. The more preferred heat treatment temperature range of the present invention is 400°C-750°C. If the temperature is too low, PVP cannot be completely removed; if the temperature is too high, the preparation time is extended and the energy consumption is too high.

[0051] Preferably, the heat treatment time in step (3) is 0.5h-5h, for example, it can be 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h or 5h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0052] Preferably, the atmosphere of the heat treatment in step (3) includes a nitrogen atmosphere.

[0053] As a preferred technical solution of the preparation method of the present invention, the preparation method comprises the following steps:

[0054] (1) placing the carbon fiber in a muffle furnace, heating the temperature to 400°C-500°C at a heating rate of 5°C / min-10°C / min, and calcining the temperature for 20min-60min to remove the glue, thereby obtaining a pretreated carbon fiber;

[0055] (2) uniformly mixing carbon nanotubes, polyvinyl pyrrolidone and water in a mass ratio of (1-2):(0.5-5):(1-10), ultrasonicating for 10 min-20 min, and using a high-pressure homogenizer for dispersion time of 20 min-30 min at a pressure of 300 bar-500 bar to obtain a CNT / PVP solution;

[0056] (3) After the pH of the solution is adjusted to 8.0-9.0 by mixing tris(hydroxymethyl)aminomethane and CNT / PVP solution, the CNT / PVP solution and dopamine hydrochloride are mixed according to the mass ratio of CNT to dopamine hydrochloride (1-2): (1-2) to obtain a CNT / PVP / DA solution; the CNT / PVP / DA solution is impregnated into the pretreated carbon fiber for 5 h-8 h, and then washed with water to remove impurities and dried at 60° C.-80° C. for 12 h-24 h to obtain a CF@PDA@CNT material;

[0057] (4) The obtained CF@PDA@CNT material is heat treated at 400°C-2000°C for 0.5h-5h in a nitrogen atmosphere of a vacuum tube furnace to obtain the carbon fiber structure battery negative electrode material.

[0058] In a third aspect, the present invention provides a negative electrode plate, wherein the negative electrode plate comprises the carbon fiber structure battery negative electrode material described in the first aspect, such as the carbon fiber structure battery negative electrode material prepared by the preparation method described in the second aspect.

[0059] The negative electrode sheet of the present invention has excellent mechanical and electrical properties, can significantly improve the problem of poor interface contact between carbon fiber negative electrode materials and resin / electrolyte materials, and can also be used as positive and negative electrode current collectors due to its excellent mechanical strength.

[0060] In a fourth aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the negative electrode sheet described in the third aspect.

[0061] The lithium ion battery provided by the present invention not only has excellent mechanical properties, but also has excellent rate performance and high specific capacity.

[0062] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0063] Compared with the prior art, the present invention has at least the following beneficial effects:

[0064] (1) The present invention selects carbon nanotubes to modify carbon fibers, and carbon nanotubes and polydopamine are coated on the surface of carbon fibers, thereby improving mechanical properties and interface properties while increasing the specific capacity of the negative electrode of the structural battery. In addition, this design can also be used for the current collector of the positive electrode of the structural battery, because compared with aluminum foil, carbon nanotube-modified carbon fibers have not only good electrical conductivity, but also excellent mechanical properties and deformation resistance of positive electrode active materials, wherein polydopamine connects carbon fibers and carbon nanotubes in the form of strong interaction between carbon fibers and carbon nanotubes, further improving the bonding force between carbon nanotubes and carbon fibers, so that they have good mechanical properties.

[0065] (2) The present invention utilizes the synergistic effect of polydopamine (PDA) and polyvinyl pyrrolidone (PVP) to comprehensively improve the mechanical properties and electrical properties of carbon fiber materials. Among them, the addition of carbon nanotubes improves the conductivity, specific surface area and interaction sites with the electrolyte of a single carbon fiber, and enhances the electronic conduction between carbon fibers in the resin electrolyte; while polyvinyl pyrrolidone promotes the dispersion of carbon nanotubes, it leaves pores in the negative electrode material after heat treatment, and the formation of pores further increases the specific surface area of ​​the carbon fiber negative electrode material, improves the wettability of the interface, and improves the contact between the electrolyte and the carbon fiber negative electrode material; in addition, the addition of PDA enhances the interface performance between the carbon fiber negative electrode material and the resin electrolyte; polydopamine can connect carbon nanotubes and carbon fibers, so that the carbon nanotubes can be tightly connected to the surface of the carbon fiber, and together with polydopamine, a stable coating layer is formed, so that the carbon nanotubes will not fall off during the battery cycle, thereby obtaining a carbon fiber negative electrode material with higher specific capacity and better rate performance.

[0066] (3) The negative electrode sheet of the present invention has excellent mechanical and electrical properties, and can significantly improve the problem of poor interface contact between carbon fiber negative electrode materials and resin materials. Its excellent mechanical strength can also be used as positive and negative electrode current collectors. The provided lithium-ion battery not only has excellent mechanical properties, but also has excellent rate performance and high specific capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0067] Figure 1 This is a schematic diagram of the structure of the CF@PDA@SWCNTs negative electrode material prepared in Example 1 of the present invention;

[0068] Figure 2 This is a schematic diagram of the process of preparing CF@PDA@SWCNTs negative electrode material in Example 1 of the present invention;

[0069] Figure 3 The SEM image and the locally enlarged morphology SEM image of the CF@PDA@SWCNTs material prepared in Example 1 of the present invention;

[0070] Figure 4 It is a bar chart of the interface shear strength of the negative electrode materials prepared in Example 1 of the present invention and Comparative Examples 1-4.

[0071] Figure 5 It is a rate performance curve diagram of the negative electrode materials prepared in Example 1, Comparative Example 1 and Comparative Example 4 of the present invention for lithium metal half-cells.

[0072] Figure 6 This is a charge and discharge curve diagram of the CF@PDA@SWCNTs sample prepared in Example 1 of the present invention during the cycle process. DETAILED DESCRIPTION

[0073] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.

[0074] In the following examples, unless otherwise specified, all reagents and consumables were purchased from conventional reagent manufacturers in the field; unless otherwise specified, the experimental methods and technical means used were conventional methods and means in the field.

[0075] Example 1

[0076] This embodiment provides a carbon fiber structure battery negative electrode material, and its specific structural schematic diagram is as follows Figure 1 As shown, the carbon fiber structure battery negative electrode material includes carbon fiber, single-walled carbon nanotube and polydopamine; the single-walled carbon nanotube and polydopamine are coated on the surface of the carbon fiber; the polydopamine connects the carbon fiber and the single-walled carbon nanotube by strong interaction between the carbon fiber and the single-walled carbon nanotube.

[0077] The schematic diagram of the preparation process of the carbon fiber structure battery negative electrode material provided in this embodiment is as follows Figure 2 As shown, the specific preparation method comprises the following steps:

[0078] (1) Carbon fiber (T700, Toray, Japan) was placed in a muffle furnace, heated to 450°C at a heating rate of 5°C / min, and calcined for 30 min to remove the glue, thereby obtaining pretreated carbon fiber;

[0079] (2) Single-walled carbon nanotubes (95% purity, OCSIAL), polyvinyl pyrrolidone (K30, Sinopharm Group) and water were uniformly mixed in a mass ratio of 1:1:1, ultrasonicated for 10 min, and dispersed for 25 min at a pressure of 400 bar using a high-pressure homogenizer (AH-BASIC 2, Suzhou Antos) to obtain a SWCNTs / PVP solution;

[0080] (3) After the pH of the solution was adjusted to 8.5 by mixing tris(hydroxymethyl)aminomethane (AR-grade, Sinopharm Group) and SWCNTs / PVP solution, the SWCNTs / PVP solution and dopamine hydrochloride (98%, Aladdin) were mixed in a mass ratio of 1:1 to obtain a SWCNTs / PVP / DA solution; the SWCNTs / PVP / DA solution was poured into a rectangular tank, the pretreated carbon fiber was fixed in the rectangular tank, and the reaction was immersed at 30°C for 6h, and then washed with water to remove impurities and dried at 60°C for 12h to obtain a CF@PDA@SWCNTs material;

[0081] (4) The obtained CF@PDA@SWCNTs material was heat treated at 500° C. for 2 h in a nitrogen atmosphere in a vacuum tube furnace to obtain the carbon fiber structure battery negative electrode material.

[0082] The SEM image of the prepared carbon fiber structure battery negative electrode material is as follows Figure 3 As shown, from Figure 3 It can be seen that under the synergistic effect of PVP and PDA, carbon nanotubes are evenly coated on the surface of carbon fibers. After pyrolysis, the carbon tubes are more clearly visible and the surface is rougher.

[0083] The shear strength of the negative electrode material obtained by testing is as follows Figure 4 As shown, the interfacial shear strength of the negative electrode material is 108.11 MPa, and the shear strength of the negative electrode material is significantly improved.

[0084] The obtained carbon fiber structure battery negative electrode material was used to assemble a button battery, and the battery rate performance was tested. Figure 5 As shown, it can be seen that the battery has excellent rate performance.

[0085] The obtained carbon fiber structure battery negative electrode material was used to assemble a button battery, and the battery's charge and discharge performance was tested. Figure 6 As shown, it can be seen that the battery has a higher charge and discharge specific capacity and capacity retention rate.

[0086] Example 2

[0087] This embodiment provides a carbon fiber structure battery negative electrode material, the carbon fiber structure battery negative electrode material comprises carbon fiber, single-walled carbon nanotubes and polydopamine; the single-walled carbon nanotubes and polydopamine are coated on the surface of the carbon fiber;

[0088] The polydopamine connects the carbon fiber and the single-walled carbon nanotube by a strong interaction between the carbon fiber and the single-walled carbon nanotube;

[0089] The method for preparing the carbon fiber structure battery negative electrode material provided in this embodiment comprises the following steps:

[0090] (1) Carbon fiber (T700, Toray, Japan) was placed in a muffle furnace, heated to 400°C at a heating rate of 8°C / min, and calcined for 60 min to remove the glue, thereby obtaining pretreated carbon fiber;

[0091] (2) Single-walled carbon nanotubes (95% purity, OCSIAL), polyvinyl pyrrolidone (K30, Sinopharm Group) and water were uniformly mixed in a mass ratio of 1:2:1, ultrasonicated for 10 min, and dispersed for 30 min at a pressure of 350 bar using a high-pressure homogenizer (AH-BASIC2, Suzhou Antos) to obtain a SWCNTs / PVP solution;

[0092] (3) After adjusting the pH of the solution to 8.0 by mixing tris(hydroxymethyl)aminomethane (AR-grade, Sinopharm Group) and SWCNTs / PVP solution, the SWCNTs / PVP solution and dopamine hydrochloride (98%, Aladdin) were mixed in a mass ratio of 1:1.5 to obtain a SWCNTs / PVP / DA solution; the SWCNTs / PVP / DA solution was poured into a rectangular tank, the pretreated carbon fiber was fixed in the rectangular tank, and the reaction was immersed at 25°C for 8h, and then washed with water to remove impurities and dried at 70°C for 12h to obtain a CF@PDA@SWCNTs material;

[0093] (4) The obtained CF@PDA@SWCNTs material was heat treated at 400°C for 5 h in a nitrogen atmosphere in a vacuum tube furnace to obtain the carbon fiber structure battery negative electrode material.

[0094] Example 3

[0095] This embodiment provides a carbon fiber structure battery negative electrode material, the carbon fiber structure battery negative electrode material comprises carbon fiber, multi-walled carbon nanotubes and polydopamine; the multi-walled carbon nanotubes and polydopamine are coated on the surface of the carbon fiber;

[0096] The polydopamine connects the carbon fibers and the multi-walled carbon nanotubes in a strong interaction between the carbon fibers and the multi-walled carbon nanotubes;

[0097] The method for preparing the carbon fiber structure battery negative electrode material provided in this embodiment comprises the following steps:

[0098] (1) placing the carbon fiber in a muffle furnace, heating the temperature to 500° C. at a heating rate of 10° C. / min, and calcining the temperature for 20 min to remove the glue, thereby obtaining a pretreated carbon fiber;

[0099] (2) uniformly mixing multi-walled carbon nanotubes (95% purity, OCSIAL), polyvinyl pyrrolidone and water in a mass ratio of 2:1:1, ultrasonicating for 10 min, and using a high-pressure homogenizer for dispersion time at a pressure of 500 bar for 20 min to obtain a MWCNTs / PVP solution;

[0100] (3) After the pH of the solution is adjusted to 9.0 by mixing tris(hydroxymethyl)aminomethane and MWCNTs / PVP solution, the MWCNT / sPVP solution and dopamine hydrochloride are mixed in a mass ratio of CNTs to dopamine hydrochloride of 2:1 to obtain a MWCNTs / PVP / DA solution; the MWCNTs / PVP / DA solution is poured into a rectangular tank, the pretreated carbon fiber is fixed in the rectangular tank, and the carbon fiber is immersed in the reaction at 30°C for 6 hours, and then washed with water to remove impurities and dried at 60°C for 12 hours to obtain a CF@PDA@MWCNTs material;

[0101] (4) The obtained CF@PDA@MWCNTs material was heat treated at 750° C. for 0.5 h in a nitrogen atmosphere in a vacuum tube furnace to obtain the carbon fiber structure battery negative electrode material.

[0102] Example 4

[0103] This embodiment provides a carbon fiber structure battery negative electrode material, which is different from Embodiment 1 only in that, when preparing the carbon fiber structure battery negative electrode material, the mass ratio of the carbon nanotubes, polyvinyl pyrrolidone and water in step (2) is 1:6:1.

[0104] Example 5

[0105] This embodiment provides a carbon fiber structure battery negative electrode material, which is different from Embodiment 1 only in that, when preparing the carbon fiber structure battery negative electrode material, the mass ratio of the carbon nanotubes, polyvinyl pyrrolidone and water in step (2) is 3:1:1.

[0106] Example 6

[0107] This embodiment provides a carbon fiber structure battery negative electrode material, which is different from Embodiment 1 only in that, when preparing the carbon fiber structure battery negative electrode material, the mass ratio of CNT to dopamine hydrochloride in the CNT / PVP solution in step (3) is 1:3.

[0108] Example 7

[0109] This embodiment provides a carbon fiber structure battery negative electrode material, which is different from Embodiment 1 only in that, when preparing the carbon fiber structure battery negative electrode material, the mass ratio of CNT to dopamine hydrochloride in the CNT / PVP solution in step (3) is 3:1.

[0110] Example 8

[0111] This embodiment provides a carbon fiber structure battery negative electrode material, which is different from Embodiment 1 only in that, when preparing the carbon fiber structure battery negative electrode material, the temperature of the heat treatment in step (4) is 300°C.

[0112] Example 9

[0113] This embodiment provides a carbon fiber structure battery negative electrode material, which is different from Embodiment 1 only in that when preparing the carbon fiber structure battery negative electrode material, the temperature of the heat treatment in step (4) is 800°C.

[0114] Example 10

[0115] This embodiment provides a carbon fiber structure battery negative electrode material, which is different from Embodiment 1 only in that, when preparing the carbon fiber structure battery negative electrode material, the temperature of the heat treatment in step (4) is 2200°C.

[0116] Comparative Example 1

[0117] This comparative example provides a negative electrode material, which differs from Example 1 only in that, when preparing the carbon fiber structure battery negative electrode material, carbon nanotubes are not added in step (2) and dopamine hydrochloride is not added in step (3), and the remaining steps remain unchanged.

[0118] The shear strength of the negative electrode material obtained by testing is as follows Figure 4 As shown, it can be seen that if carbon nanotubes are not added, the interface shear strength of the negative electrode material is 61.54 MPa, which is significantly lower than the shear strength of the carbon fiber structure battery negative electrode material obtained in Example 1.

[0119] The obtained negative electrode material was used to assemble a button battery, and the rate performance of the battery was tested. Figure 5 As shown, it can be seen that if carbon nanotubes and dopamine hydrochloride are not added, the rate performance of the battery assembled with the obtained negative electrode material is significantly lower than that in Example 1.

[0120] Comparative Example 2

[0121] This comparative example provides a negative electrode material, which is different from Example 1 only in that when preparing the carbon fiber structure battery negative electrode material, carbon nanotubes are not added in step (2), and the other steps remain unchanged.

[0122] The shear strength of the negative electrode material obtained by testing is as follows Figure 4 As shown, it can be seen that if carbon nanotubes are not added, the interface shear strength of the negative electrode material is 86.87 MPa, which is significantly lower than the shear strength of the carbon fiber structure battery negative electrode material obtained in Example 1.

[0123] Comparative Example 3

[0124] This comparative example provides a negative electrode material, which is different from Example 1 only in that, when preparing the carbon fiber structure battery negative electrode material, dopamine hydrochloride is not added in step (3), and the other steps remain unchanged.

[0125] The shear strength of the negative electrode material obtained by testing is as follows Figure 4 As shown, it can be seen that if dopamine hydrochloride is not added, the interface shear strength of the negative electrode material is 92.09 MPa, which is significantly lower than the shear strength of the carbon fiber structure battery negative electrode material obtained in Example 1.

[0126] Comparative Example 4

[0127] This comparative example provides a negative electrode material, which is different from Example 1 only in that when preparing the carbon fiber structure battery negative electrode material, the heat treatment of step (4) is not performed, and the other steps remain unchanged.

[0128] The shear strength of the negative electrode material obtained by testing is as follows Figure 4As shown, it can be seen that if the heat treatment in step (4) is not performed, the interface shear strength of the negative electrode material is 102.97 MPa, which is significantly lower than the shear strength of the carbon fiber structure battery negative electrode material obtained in Example 1.

[0129] The obtained negative electrode material was used to assemble a button battery, and the rate performance of the battery was tested. Figure 5 As shown, it can be seen that if carbon nanotubes are not added, the rate performance of the battery assembled with the obtained negative electrode material is significantly lower than that in Example 1.

[0130] Comparative Example 5

[0131] This comparative example provides a negative electrode material, which is different from Example 1 only in that when preparing the carbon fiber structure battery negative electrode material, polyvinyl pyrrolidone is not added in step (2), and the other steps remain unchanged.

[0132] Comparative Example 6

[0133] This comparative example provides a negative electrode material, which is different from Example 1 only in that when preparing the carbon fiber structure battery negative electrode material, step (3) is prepared by the method disclosed in patent CN117166019A.

[0134] Test method: Cut the carbon fiber negative electrode materials obtained in Examples 1-10 and Comparative Examples 1-6 into multiple 1*0.8cm small strips, and prepare a stable electrode sheet with PVDF binder (MTI,>99.5%) (fiber to PVDF mass ratio 9:1). Then, in the glove box, install the button battery according to the steps of negative electrode shell→fiber electrode sheet→fiber diaphragm→lithium metal sheet→gasket→shrapnel→positive electrode shell.

[0135] The test results show that: at 0.5C, the battery's first discharge capacity and the battery's capacity after 100 charge and discharge cycles were tested, wherein the electrolyte used 1M LiPF6 in DEC:EC:EMC=2:1:2wt%.

[0136] Table 1

[0137]

[0138]

[0139] The test results show that:

[0140] (1) It can be seen from Examples 1-3 that the present invention selects carbon nanotubes to modify carbon fibers, and utilizes the synergistic effect of polydopamine (PDA) and polyvinylpyrrolidone (PVP) to comprehensively improve the mechanical properties and electrical properties of carbon fiber materials.

[0141] (2) By comparing Example 1 with Examples 4-5, it can be seen that the present invention further controls the mass ratio of carbon nanotubes, polyvinyl pyrrolidone and water to (1-2):(0.5-5):(1-10) to obtain a uniformly dispersed carbon nanotube dispersion. By adjusting the mass ratio of carbon nanotubes and polyvinyl pyrrolidone, the dispersion state of the carbon nanotubes in the dispersion and the distribution state on the carbon fibers at a later stage can be controlled.

[0142] (3) By comparing Example 1 with Examples 6-7, it can be seen that the present invention further regulates the progress of the subsequent reaction and the thickness of the coating layer by setting the mass ratio of CNT to dopamine hydrochloride in the CNT / PVP solution to (1-2):(1-2). At the same time, since the polydopamine generated by the reaction acts as a bridge between the carbon nanotubes and the carbon fibers to connect them, the amount of dopamine hydrochloride added will affect the stability of the coating layer. When the amount of dopamine hydrochloride added is too much, the thickness of the coating layer will be too thick, and the excess polydopamine will form a coating layer on the outer layer of the carbon nanotubes, which will hinder the transmission of electrons and is not conducive to the improvement of the conductivity of the negative electrode material.

[0143] (4) By comparing Example 1 with Examples 8-10, it can be seen that the present invention further removes unreacted impurities through heat treatment and completely removes PVP to form a porous structure on the surface of the carbon fiber. In addition, within this temperature range, part of the polydopamine can undergo graphitization, which can further improve the conductivity of the carbon fiber negative electrode material. The more preferred temperature range of the present invention is 400°C-750°C. If the temperature is too low, PVP cannot be completely removed; if the temperature is too high, the preparation time is extended and the energy consumption is too high.

[0144] (5) It can be seen from Example 1 and Comparative Example 1 that the present invention can obtain excellent mechanical and electrical properties by simultaneously introducing carbon nanotubes and polydopamine, while when carbon nanotubes and polydopamine are not used to coat carbon fibers, the mechanical and electrical properties of the obtained negative electrode material are significantly reduced.

[0145] (6) It can be seen from Example 1 and Comparative Example 2 that the present invention can significantly improve the mechanical strength of the carbon fiber negative electrode by introducing carbon nanotubes. When carbon nanotubes are added, the shear strength of the negative electrode material is significantly reduced, and the electrical performance of the assembled battery is also significantly reduced.

[0146] (7) It can be seen from Example 1 and Comparative Example 3 that when dopamine hydrochloride is not added, the shear strength of the electrode is greatly reduced, the mechanical and interface properties of the battery are reduced, and the service life is even lower.

[0147] (8) It can be seen from Example 1 and Comparative Example 4 that the present invention can improve the conductivity and mechanical properties of the carbon fiber negative electrode material by further heat treatment. When no heat treatment is performed, it is impossible to achieve the transformation of the polydopamine crystal form, and the conductivity of the negative electrode material is not as good as that of the material after heat treatment.

[0148] (9) It can be seen from Example 1 and Comparative Example 5 that the present invention introduces PVP as a dispersant. PVP is more environmentally friendly and easy to obtain, and the material cost is lower. On the other hand, PVP can be removed in the subsequent heat treatment stage, thereby leaving pores in the negative electrode material. The formation of pores increases the specific surface area of ​​the carbon fiber negative electrode material, improves the wettability of the interface, and thus improves the contact between the electrolyte and the carbon fiber negative electrode material.

[0149] (10) It can be seen from Example 1 and Comparative Example 6 that the present invention impregnates the mixed CNT / PVP / DA solution into the pretreated carbon fiber, and during the impregnation, dopamine hydrochloride undergoes a polymerization reaction. During the reaction, polydopamine can connect the carbon nanotubes and the carbon fiber, so that the carbon nanotubes can be tightly connected to the surface of the carbon fiber, and together with the polydopamine, a firm and stable coating layer is formed. The carbon nanotubes will not fall off during the battery cycle, thereby improving the stability of the coating layer. If the CNT / DA solvent is allowed to complete the polymerization reaction, and then the CNT / PDA solution obtained by the reaction is deposited on the carbon fiber by electrophoretic deposition technology, this process is to first obtain carbon nanotubes coated with polydopamine, and then deposit the carbon nanotubes coated with polydopamine on the carbon fiber by electrophoretic deposition. The carbon fiber obtained by this method only contains a coating layer of carbon nanotubes, and the electrophoretic deposition method can only make the carbon fiber adsorb on the surface of the carbon fiber. Without polydopamine as an intermediate connecting bridge, a firm coating layer cannot be formed.

[0150] In summary, the present invention improves the mechanical properties and electrical properties of carbon fiber materials by utilizing the synergistic effect of polydopamine (PDA) and polyvinyl pyrrolidone (PVP). Among them, the addition of carbon nanotubes improves the conductivity of a single carbon fiber and enhances the electronic conduction between carbon fibers in the resin electrolyte; while polyvinyl pyrrolidone promotes the dispersion of carbon nanotubes, it leaves pores in the negative electrode material after heat treatment, and the formation of pores increases the specific surface area of ​​the carbon fiber negative electrode material, improves the wettability of the interface, and improves the contact between the electrolyte and the carbon fiber negative electrode material; in addition, the addition of PDA enhances the interface performance between the carbon fiber negative electrode material and the resin electrolyte; polydopamine can connect carbon nanotubes and carbon fibers, so that the carbon nanotubes can be tightly connected to the surface of the carbon fiber, and together with polydopamine, a stable coating is formed, and the carbon nanotubes will not fall off during the battery cycle, thereby obtaining a carbon fiber negative electrode material with higher specific capacity and better rate performance.

[0151] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A carbon fiber structure battery negative electrode material, characterized in that: The carbon fiber structure battery negative electrode material comprises carbon fiber, carbon nanotube and polydopamine; the carbon nanotube and polydopamine are coated on the surface of the carbon fiber to form a carbon nanotube and polydopamine coating layer; The polydopamine connects the carbon fibers and the carbon nanotubes through a strong interaction between the carbon fibers and the carbon nanotubes.

2. The carbon fiber structure battery negative electrode material according to claim 1, characterized in that: The carbon fiber structure battery negative electrode material has a porous structure; Preferably, the thickness of the carbon nanotube and polydopamine coating layer is 20-250 nm; Preferably, the carbon nanotubes include single-walled carbon nanotubes or multi-walled carbon nanotubes.

3. A method for preparing a carbon fiber structure battery negative electrode material as claimed in claim 1 or 2, characterized in that: The preparation method comprises the following steps: (1) uniformly mixing carbon nanotubes, polyvinyl pyrrolidone and water to obtain a CNT / PVP solution; (2) mixing a pH buffer with a CNT / PVP solution, adjusting the pH of the solution, and then adding dopamine hydrochloride to obtain a CNT / PVP / DA solution; immersing the pretreated carbon fiber in the CNT / PVP / DA solution, reacting, washing, and drying to obtain a CF@PDA@CNT material; (3) The obtained CF@PDA@CNT material is subjected to heat treatment to obtain the carbon fiber structure battery negative electrode material.

4. The preparation method according to claim 3, characterized in that: The mass ratio of the carbon nanotubes, polyvinyl pyrrolidone and water is (1-2):(0.5-5):(1-10); Preferably, the diameter of the carbon nanotube is 7nm-20nm; Preferably, the length of the carbon nanotubes is 10 μm-200 μm; Preferably, the mixing method includes ultrasound and high-pressure homogenization dispersion; Preferably, the ultrasonic time is 10min-20min; Preferably, the pressure dispersed by the high-pressure homogenizer is 300 bar-500 bar; Preferably, the dispersion time of the high-pressure homogenizer is 20 min-30 min.

5. The preparation method according to claim 3 or 4, characterized in that: The method for pretreating carbon fiber comprises the following steps: The carbon fiber is heated to 400-500°C at a heating rate of 5-10°C / min, and calcined for 20-60 minutes to remove the glue, thereby obtaining the pretreated carbon fiber.

6. The preparation method according to any one of claims 3 to 5, characterized in that: The pH buffer in step (2) comprises tris(hydroxymethyl)aminomethane; Preferably, the pH of the solution is adjusted to 8.0-9.0; Preferably, the mass ratio of CNT to dopamine hydrochloride in the CNT / PVP / DA solution is (1-2):(1-2); Preferably, the impregnation reaction temperature is 25°C-40°C; Preferably, the impregnation reaction time is 5h-8h; Preferably, the cleaning solvent in step (2) comprises water; Preferably, the drying temperature in step (2) is 60°C-80°C; Preferably, the drying time in step (2) is 12h-24h.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The temperature of the heat treatment in step (3) is 400°C-2000°C, preferably 400°C-750°C; Preferably, the heat treatment time in step (2) is 0.5h-5h; Preferably, the atmosphere of the heat treatment in step (2) includes a nitrogen atmosphere.

8. The preparation method according to any one of claims 3 to 7, characterized in that: The preparation method comprises the following steps: (1) placing the carbon fiber in a muffle furnace, heating the temperature to 400°C-500°C at a heating rate of 5°C / min-10°C / min, and calcining the temperature for 20min-60min to remove the glue, thereby obtaining a pretreated carbon fiber; (2) uniformly mixing carbon nanotubes, polyvinyl pyrrolidone and water in a mass ratio of (1-2):(0.5-5):(1-10), ultrasonicating for 10 min-20 min, and using a high-pressure homogenizer for dispersion time of 20 min-30 min at a pressure of 300 bar-500 bar to obtain a CNT / PVP solution; (3) After the tris(hydroxymethyl)aminomethane and CNT / PVP solution are mixed to adjust the pH value of the solution to 8.0-9.0, the CNT / PVP solution and dopamine hydrochloride are mixed according to the mass ratio of CNT to dopamine hydrochloride (1-2): (1-2) to obtain a CNT / PVP / DA solution; the pretreated carbon fiber is immersed in the CNT / PVP / DA solution for 5h-8h, washed with water to remove impurities, and dried at 60°C-80°C for 12h-24h to obtain a CF@PDA@CNT material; (4) The obtained CF@PDA@CNT material is heat treated at 400°C-2000°C for 0.5h-5h in a nitrogen atmosphere of a vacuum tube furnace to obtain the carbon fiber structure battery negative electrode material.

9. A negative electrode plate, characterized in that: The negative electrode plate comprises the carbon fiber structure battery negative electrode material according to claim 1 or 2, or the carbon fiber structure battery negative electrode material prepared by the preparation method according to any one of claims 3-8.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the negative electrode sheet according to claim 9.

Citation Information

Patent Citations

  • Method for preparing carbon nanotube-polydopamine embedded composite coating through electrophoretic deposition

    CN117166019A

  • Surface modified carbon fiber, preparation method thereof and application of surface modified carbon fiber in reinforced resin-based composite material

    CN116949814A

  • Carbon fiber-carbon nanotube three-dimensional conductive agent and battery thereof

    CN117199371A

  • Omitted

    KR1020170057611A

  • Negative electrode material for nonaqueous electrolyte secondary battery, and preparation method therefor

    WO2022021933A1